Efektifitas Black Garlic Sebagai Adsorben Untuk Menurunkan Kadar Asam Lemak Bebas dan Bilangan Peroksida Pada Minyak Goreng Bekas - Gultom, Erdiana; Hestina (Universitas Sari Mutiara Indonesia, 2023)
In this Research, black garlic was used as an adsorbent to reduce levels of free fatty accids (ALB) and peroxide value in used cooking oil. The research aims to determine levels of free fatty accids (ALB) and peroxide value of used cooking oil before friying (sample A), three times (B), four times(C) and five times (D) friying before and after adding black garlic adsorbent. This research used a laboratory scale exsperimental method. To determine of free fatty acids (ALB) using by alkalimetry titration method, while to determine of peroxide value using bg iodometry method. Based on the result of the research it was found that the highest decrease of free fatty accids (ALB) was sample D, where before adding black garlic adsorbent the free fatty accids (ALB) was 1,0468% and after adding black garlic adsorbent the free fatty accids (ALB) 0,1427%. While the highest decrease of peroxide value was sample D, where peroxide value of sample D before adding black garlic adsorbent was 4,8526 meg/kg and after adding the black garlic adsorbent the peroxide value be 1,1021 meq/kg.